The Finger of God : Enoch Mgijima, the Israelites, and the Bulhoek Massacre in South Africa - Edgar, Robert R. (Book collections on Project MUSE., 2018)
"This book analyzes the South African government's 1921 massacre of Enoch Mgijima's "Israelites," who refused to vacate land on which they were waiting for the end of the world, as both a signal event in South African history and an example of government conflicts with millennial movements worldwide."--Publisher's summary